‫آليات ‬‫الرقابة‬ ‫الضربية‬ ‫و‬ ‫دورها‬‫ في‬ ‫تعزيز‬ ‫الوظيفة‬ ‫الجبائية‬ ‫في‬ ‫المؤسسة‬ ‫اﻻقتصادية‬‫–‬ ‫دراسة‬ ‫حالة‬ ‫–‬ ‫مركز‬ ‫الضرائب‬ ‫سوق‬ ‫أهراس - ‬‫عبد‬ ‫السﻼم ‫دغوش ‬; ‬‫مصطفى اوﻻصب ‬ (My University, 2019)
This study attempts to investigate the role of Fiscal Control Mechanism in enhancing the Fiscal Function in the economic institutions by recognizing the various types of Fiscal Control, Audit Investigation, Targeted investigation and Over-all Investigation in diagnosing the tax risks depending on the case study of Souk Ahras’ tax center. This study reached that Fiscal Control mechanism has an important impact in recognizing and analyzing the risks and deficiencies that faces the institute due to tax irregularities or the misuse of different privileges and motivations accorded by the criminal legislation and work on avoiding it in the future. .................................................. تحاول هذه الدراسة دراسة دور الرقابة المالية آلية تعزيز الوظيفة المالية في الاقتصاد المؤسسات من خلال التعرف على أنواع مختلفة من الرقابة المالية والتدقيق التحقيق والتحقيق المستهدف والتحقيق الشامل في تشخيص المخاطر الضريبية اعتمادا على دراسة حالة سوق أهراس مركز الضرائب. وتوصلت هذه الدراسة إلى أن آلية الرقابة المالية لديها تأثير مهم في التعرف على المخاطر وتحليلها أوجه القصور التي تواجه المعهد بسبب المخالفات الضريبية أو إساءة استخدام الامتيازات والدوافع المختلفة التي يمنحها المجرم التشريعات والعمل على تجنبها مستقبلا. الكلمات المفتاحية: الخطر الجنائي، المراجعة الجزائية، الامتيازات المالية، الرقابة المالية.
‬